EGMR 4976/20 vom 13. Februar 2024 , CASE OF JANN-ZWICKER AND JANN v. SWITZERLAND - Hudoc Ch (2024)
Violation of Article 6 - Right to a fair trial (Article 6 - Civil proceedings;Article 6-1 - Access to court);Violation of Article 6 - Right to a fair trial (Article 6 - Civil proceedings;Article 6-1 - Reasonable time);Pecuniary damage - claim dismissed (Article 41 - Pecuniary damage;Just satisfaction);Non-pecuniary damage - award (Article 41 - Non-pecuniary damage;Just satisfaction); Violation: 6;6-1